2009
DOI: 10.1093/humrep/dep377
|View full text |Cite
|
Sign up to set email alerts
|

Randomized placebo-controlled trial of CDB-2914 in new users of a levonorgestrel-releasing intrauterine system shows only short-lived amelioration of unscheduled bleeding

Abstract: The effect of CDB-2914 on BS% was initially beneficial but then by third treatment was disadvantageous. Nevertheless, only 3% (4/136) of all women discontinued LNG-IUS. These findings give insight into possible mechanisms and suggest future research directions. ISRCTN Trial no. ISRCTN58283041; EudraCT no. 2006-006511-72.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 15 publications
0
23
1
1
Order By: Relevance
“…Questionnaires are outlined in the footnotes to table 1—they are based on those used in previous studies 1328 29 The study doctors and in particular study nurses will develop excellent rapport with patients to maximise completeness of data collected.…”
Section: Design and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Questionnaires are outlined in the footnotes to table 1—they are based on those used in previous studies 1328 29 The study doctors and in particular study nurses will develop excellent rapport with patients to maximise completeness of data collected.…”
Section: Design and Methodsmentioning
confidence: 99%
“…The Levonorgestrel intrauterine system (LNG-IUS), a hormonal contraceptive now licensed as treatment for HMB, is unsuitable for women seeking to become pregnant. LNG-IUS can cause amenorrhoea, or for other users there is ongoing and unpredictable unscheduled bleeding, and these consequences can be unacceptable to women 13. The audit reported that in the first year after attendance for HMB, oral medication and IUS were received by 29% and 33%, respectively, but these were the ‘final’ treatment for only 12% (over half switched from oral medication) and 22% (one third switched from IUS) 11.…”
Section: Introductionmentioning
confidence: 99%
“…With ongoing treatment, the placebo group appeared to have a more favourable bleeding pattern, even though there were no significant differences in acceptability measures. 79 This study highlighted the important difference between prevention and treatment of an undesired side effect and concluded that there is possibly more potential for PRMs to improve than to prevent unscheduled bleeding in users of POC. 79…”
Section: Contraceptionmentioning
confidence: 96%
“…78 However, suppression of unscheduled bleeding has not been consistently demonstrated, and the implications for contraceptive efficacy also remain to be clarified. 79,80 One study administering CDB-2914 to new LNG-IUS users in an attempt to prevent breakthrough bleeding found that the initial beneficial effect was temporary. With ongoing treatment, the placebo group appeared to have a more favourable bleeding pattern, even though there were no significant differences in acceptability measures.…”
Section: Contraceptionmentioning
confidence: 99%
“…By the third cycle, ulipristal treatment was associated with an increase in bleeding and spotting days, equivalent to 6 extra days. 22 …”
Section: Selective Progesterone Receptor Modulatorsmentioning
confidence: 99%